2000
DOI: 10.1002/(sici)1097-0274(200002)37:2<159::aid-ajim1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and risk of malignant pleural mesothelioma: A case-control study in Spain

Abstract: Background The association of mesothelioma and asbestos exposure is well known, but some data suggest that probably many people are still being exposed to asbestos without knowing it. Methods Between 1993 and 1996, 132 cases (77% males) of histologically con®rmed malignant pleural mesothelioma and 257 controls, residents in two provinces of Spain (Barcelona and Ca Âdiz), were interviewed. They were classi®ed according to their probability and intensity of occupational asbestos exposure by a panel of industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
3

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 22 publications
(22 reference statements)
9
42
3
Order By: Relevance
“…In more than 70% of cases, occupational asbestos exposure was established [98,65,2]. The highest pulmonary asbestos burden and the shortest latency period was shown, as in other studies [13,74], to be in workplaces in the asbestos and insulation industries, and in shipyards.…”
Section: Latency Period and Work Historysupporting
confidence: 56%
See 2 more Smart Citations
“…In more than 70% of cases, occupational asbestos exposure was established [98,65,2]. The highest pulmonary asbestos burden and the shortest latency period was shown, as in other studies [13,74], to be in workplaces in the asbestos and insulation industries, and in shipyards.…”
Section: Latency Period and Work Historysupporting
confidence: 56%
“…The age distribution in our study shows a maximum between 54 and 62 years [80,91,2]. There are no differences in age distribution between men and women.…”
Section: Age Distributionsupporting
confidence: 41%
See 1 more Smart Citation
“…Teschke et al (1997) reported a higher percentage of interviews by family members for cases than controls (33.3 vs. 13.6%). Similarly, Agudo et al (2000) reported that 55.3% cases and 99.6% controls were interviewed in their study. A potential concern is that family members might not be able to recall all the jobs of the study subjects (cases or controls), especially jobs of very short duration and that jobs including those involving brake exposure might have been underreported.…”
Section: Interview or Recall Biasmentioning
confidence: 84%
“…In the Agudo et al study,22.0% interviews were provided by the subjects' spouses. Agudo et al (2000) cited a validation study by Bond et al (1988), which shows that "information on number of areas and usual work area assignment provided by the spouse performed quite well when compared with the subject itself." In the Agudo et al study, the agreement between the subjects' and the spouses' recalls was very high ( D 0.79).…”
Section: Interview or Recall Biasmentioning
confidence: 99%